Environmental psychology - Heimstra, Norman W. (California : Brooks/Cole Publishing Company, 1974)
The purpose of this book is to present a brief overview of basic concepts and major concerns in the field that has become known as environmental psychology. The central issue of this newly emerging field is the various relationships between the physical environment and man's behavior.
McFarling, Leslie H.
Keywords: ENVIRONMENTAL PSYCHOLOGY